‘Radio Studies’ in Spain. Three decades of research in academic Communication journals (1980-2013) - Teresa Piñeiro Otero (Estudios sobre el Mensaje Periodístico, 2015)
The communication research in Spain has lived a major expansion in recent decades. This evolution has not been balanced; it has enhanced certain topics and approaches over others. Knowing this context, this article aims to conduct a longitudinal analysis of radio scientific production published in Spanish Communication journals between 19802013. This analysis has focused on the evolution of the publication of articles on radio, main topics and approaches of the research and theoretical methodological guidance of these contributions and evolution over three decades. These variables have allowed making a critical approach on radio research in Spain..